2003
DOI: 10.1091/mbc.e03-04-0247
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cdc42p GTPase-activating Proteins in Assembly of the Septin Ring in Yeast

Abstract: The septins are a conserved family of GTP-binding, filament-forming proteins. In the yeast Saccharomyces cerevisiae, the septins form a ring at the mother-bud neck that appears to function primarily by serving as a scaffold for the recruitment of other proteins to the neck, where they participate in cytokinesis and a variety of other processes. Formation of the septin ring depends on the Rho-type GTPase Cdc42p but appears to be independent of the actin cytoskeleton. In this study, we investigated further the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
281
2
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(316 citation statements)
references
References 81 publications
22
281
2
8
Order By: Relevance
“…The idea that there may be multiple types of septin structures (rings and gauzes) is consistent with the observation that exchange of septin subunits changes dramatically during the cell cycle (Caviston et al, 2003;Dobbelaere et al, 2003). Both rings ( Figure 7C) and gauzes (Figure 8) consist of filaments organized into a mesh-like structure.…”
Section: Function and Ultrastructure Of Yeast Septin Networksupporting
confidence: 85%
“…The idea that there may be multiple types of septin structures (rings and gauzes) is consistent with the observation that exchange of septin subunits changes dramatically during the cell cycle (Caviston et al, 2003;Dobbelaere et al, 2003). Both rings ( Figure 7C) and gauzes (Figure 8) consist of filaments organized into a mesh-like structure.…”
Section: Function and Ultrastructure Of Yeast Septin Networksupporting
confidence: 85%
“…The septin dependence of Bnr1p provides a likely explanation for the synthetic lethality between defects in Bni1p function and septins (Longtine et al, 1996), which recapitulate the lethality of the simultaneous loss of Bni1p-and Bnr1p-dependent cable assembly ( Figure 5A). Septindependent recruitment of Bnr1p also might explain the delay in Bnr1p recruitment to the bud neck until after bud emergence, because during this transition the septins undergo significant changes in their organization (reviewed in Gladfelter et al, 2001; recent results in Caviston et al, 2003;Dobbelaere et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae in G1, an apparent cap, or patch, of septins in which the subunits are highly mobile as judged by fluorescence recovery after photobleaching (FRAP) experiments [47,48] accumulates in the juxta-membrane region immediately subtending the incipient bud site. Septins seem to be more concentrated at the edge of this patch than at its center.…”
Section: Regulation Of Septin Polymerizationmentioning
confidence: 99%
“…In the next cell cycle, the initial recruitment of the septin patch to the incipient bud site and its transition into a rimmed disk depends on function of the small, Rho-family GTPase, Cdc42 (Reviewed in [61]). It has been reported that the effects of Cdc42 require the conversion of Cdc42-GTP to Cdc42-GDP [64], via the action of either the cognate Cdc42-GAPs (Rga1, Rga2 and Bem3) [47] or, as yet, unknown effectors [65].…”
Section: Phosphorylation Exerts Temporal Control On Septin-collar Assmentioning
confidence: 99%